2020
DOI: 10.3324/haematol.2020.250761
|View full text |Cite
|
Sign up to set email alerts
|

Targeting shear gradient activated von Willebrand factor by the novel single-chain antibody A1 reduces occlusive thrombus formation <i>in vitro</i>

Abstract: Intraluminal thrombus formation precipitates conditions such as acute myocardial infarction and disturbs local blood flow resulting in areas of rapidly changing blood flow velocities and steep gradients of blood shear rate. Shear rate gradients are known to be pro-thrombotic with an important role for the shear-sensitive plasma protein von Willebrand factor (VWF). Here, we developed a single-chain antibody (scFv) that targets a shear gradient specific conformation of VWF to specifically inhibit platelet adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Previous studies supported this observation, as blood was recommended to use immediately or within 2 h of collection. [27,[32][33][34][35] The effect of blood age was also checked in the device with 15% stenosis, and the results showed a similar pattern (Figure S2, Supporting Information).…”
Section: Effect Of Blood Age On Thrombus Formationmentioning
confidence: 66%
“…Previous studies supported this observation, as blood was recommended to use immediately or within 2 h of collection. [27,[32][33][34][35] The effect of blood age was also checked in the device with 15% stenosis, and the results showed a similar pattern (Figure S2, Supporting Information).…”
Section: Effect Of Blood Age On Thrombus Formationmentioning
confidence: 66%
“…In support of the current data, we and others have previously shown that the role of GPIbα in flow-dependent platelet aggregation was most prominent at high pathological wall-shear rate gradients, i.e., as present at stenotic sites in the arterial circulation [46,47]. A recently published single-chain antibody, scFV-A1, designed to target VWF activated by shear, was shown to play an inhibiting effect in stenotic chambers, i.e., at sites of sharp shear rate changes [48]. Therefore, stenotic flow chambers may be a useful tool to further study the effects of the present cyclic peptides under conditions of pathological VWF-dependent platelet activation.…”
Section: Role Of Vwf A1 Domain In Shear-dependent Platelet Aggregatio...mentioning
confidence: 93%
“…When blood interacts with a foreign material, a rapid absorption of plasma protein occurs. This is believed to be the precursor of thrombosis, as it involved an aggregation of platelets and fibrin on the surface, trapping RBCs (Hoefer et al, 2020). In laminar conditions, velocity and concentration gradients, together with collisions, spontaneously transport the platelets towards the walls, enhancing these interactions.…”
Section: Mechanisms Of Shear-induced Thrombosismentioning
confidence: 99%
“…It is understood that immobilized VWF is likely to remain in its unfolded conformation at shear rates around 3,000 s -1 whereas an elongation of soluble VWF needs higher shear up to 5,000 s -1 (Siedlecki et al, 1996;Kuwahara et al, 2002;Schneider et al, 2007). However, recent observations have questioned the existence of such a threshold, showing in particular that VWF could be involved at lower shear magnitudes of, around 1,500 s -1 (Receveur et al, 2020) and in the context of shear rate gradients (Hoefer et al, 2020;Van Rooij et al, 2021). In a shear gradient context, it was observed that VWF unfolding increased at two-fold lower flow rates when compared to constant shear flows (Zhang, 2009;Sing and Alexander-katz, 2010).…”
Section: Disturbed and Elongated Shear Rate: Microgradientsmentioning
confidence: 99%